Astrocyte DNA damage and response upon acute exposure to ethanol and corticosterone - Reyes-Ábalos, Ana Laura; Álvarez-Zabaleta, Magdalena; Olivera-Bravo, Silvia; Di Tomaso, María Vittoria (Frontiers in Toxicology, 2024)
Astrocytes are the glial cells responsible for brain homeostasis, but if injured, they could damage neural cells even deadly. Genetic damage and DNA-damage response (DDR), which downstream cascades regulate the cell cycle allowing DNA repair, and probably, a wider cell reaction, are dramatic events poorly studied in astrocytes. Here, we proposed that 1 h of 400 mmol/L ethanol (EtOH) and/or 1 µmol/L corticosterone (CTS) exposure of cultured hippocampal astrocytes damages DNA activating the DDR and eliciting functional changes. Immunolabeling against γH2AX (chromatin DNA-damage sites); Cyclin D1 (cell cycle control); nuclear (base excision repair, BER) and cytoplasmic (anti-inflammatory functions) APE1; ribosomal proteins (nucleolus number), together with GFAP and S100β plus scanning electron microscopy studies of the astrocyte surface were carried out. Results indicate significant DNA damage, immediate cell cycle arrest, and BER activation. Changes in cytoplasmic signals of Cyclin D1 and APE1, in nucleolus number and in the membrane-attached vesicles, strongly suggest a reactivity-like astrocyte response without significant morphological changes. Thus, obtained data uncover astrocyte genome immediate vulnerability and DDR activation plus a functional response that could in part be signaled through extracellular vesicles, evidencing the complex influence that astrocytes may have on the CNS even upon short-term aggressions.